Microplastics in the wastewater treatment plants (WWTPs): Occurrence and removal. (November 2019) - Xu, Xia; Jian, Yun; Xue, Yingang; Hou, Qingtong; Wang, LiPing
Abstract: WWTPs may be one of the important ways for MPs to enter surface water. In the present study, the influent and effluent from eleven WWTPs in Changzhou were collected and analyzed. At the same time, the abundance, size, color, and shape of MPs in influent and effluent were investigated. The average abundance of MPs in the influent and effluent were 196.00 ± 11.89 n/L and 9.04 ± 1.12 n/L respectively, and the MPs removal efficiency of eleven WWTPs was almost over 90% in which it could be up to 97.15%. MPs were divided into four particle size based on abundance changes, and the size of MPs with the highest abundant was mainly concentrated at 0.1–0.5 mm. Among these MPs, fibers were the main shape in wastewater, followed by fragments, flakes, spheres and films. The colors of MPs in wastewater were various and 14 types of plastics were detected from wastewater using attenuated total reflection Fourier transform infrared spectroscopy (ATR-FTIR). Moreover, Rayon and PET were the dominant polymer types in eleven WWTPs. The research results provided basic data for the research and supervision of MPs pollution in WWTPs. Highlights: First comparison of MPs in eleven WWTPs from Changzhou, China. Fiber MPs were the main shape and the proportion of MPs with the size of 0.1–0.5 mm was the largest in eleven WWTPs. MPs removal efficiency of eleven WWTPs was almost over 90%. Rayon and PET were the dominant polymer types in eleven WWTPs.